Ieee Infocom 2004
DOI: 10.1109/infcom.2004.1354500
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic HLR location management scheme for PCS networks

Abstract: Abstract-In this paper, a dynamic HLR (Home Location Register) scheme for location management in PCS (Personal Communications Service) networks is presented. The proposed scheme provides a dynamic copy of mobile terminal location information in the nearest (current) HLR database. A modified table lookup procedure is also proposed for determining the current HLR easily. It allows the location registration and call delivery to be performed efficiently. An analytical model is developed for studying the performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Home location register (HLR) is connected to a lot of VLRs. Table 1 illustrates the detailed description of how the traditional registration is done [6]; it's also illustrated in Fig. 1.…”
Section: Pcs Network Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…Home location register (HLR) is connected to a lot of VLRs. Table 1 illustrates the detailed description of how the traditional registration is done [6]; it's also illustrated in Fig. 1.…”
Section: Pcs Network Architecturementioning
confidence: 99%
“…Permanent data (e.g., profile information, directory number, current location, and validation period) of the MTs whose primary subscription is within a certain SA is stored in the HLR serving such SA [6]. For each MT, HLR contains a pointer to the VLR serving the RA where such MT is currently located to assist routing incoming calls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LA is a cluster of cells (small unit of the coverage area, if any). The one or more than one Base Station (BS) can serve each cell or LA and it is fixed (Li et al, 2004). It is capable to communicate with the MT using it radio transceiver, such as cellular telephones.…”
Section: Pcs System Architecture and Related Workmentioning
confidence: 99%
“…Lots of work has been carried out to improve the QoS of LM scheme; one of them is prediction based scheme. The Akyldiz and Wang (2002) and Li et al (2004), the authors suggested new methodology for the prediction based LM scheme. The authors have assumed that there are two systems or LA (i.e X and Y) for movement of the MT, and the MT moves from X to Y.…”
Section: Pcs System Architecture and Related Workmentioning
confidence: 99%